2013
DOI: 10.1371/journal.pone.0075156
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reproducibility of a Food Frequency Questionnaire as a Measure of Recent Dietary Intake in Young Adults

Abstract: This research assessed the relative validity and reproducibility of the Dietary Questionnaire for Epidemiological Studies (DQESV2) over one month in young adults, given the lack of concise and convenient instruments for assessing recent dietary intake in this population. Participants were recruited from a large Australian university (N = 102; 35% male; age 18–34 years; body mass index 16–37 kg/m2). Five one-day weighed food records (WFR) were administered over one month followed by the DQESV2. Estimates for nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
57
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 16 publications
9
57
1
Order By: Relevance
“…The FFQ overestimated as well as underestimated the absolute intake of various nutrients and foods, which was comparable to other validation studies [29,30]. We observed that in general, frequently consumed foods tended to be overestimated in the FFQ compared to the 4-d FR, in particular vegetables and fruit intake, as reported in other FFQ validation studies [13,31]. Food items consumed daily (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…The FFQ overestimated as well as underestimated the absolute intake of various nutrients and foods, which was comparable to other validation studies [29,30]. We observed that in general, frequently consumed foods tended to be overestimated in the FFQ compared to the 4-d FR, in particular vegetables and fruit intake, as reported in other FFQ validation studies [13,31]. Food items consumed daily (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Hebden et al (4) looked at the agreement between the DQES v2 FFQ and a 5-d WFR for measuring servings of fruit and vegetables in young adults and found that vegetable intake was under-estimated by the FFQ (men: 1·6 servings; women: 2 servings) and fruit was over-estimated by the FFQ (men: 0·4 servings; women: 0·1 servings), which is comparable with that observed in the present study. We have previously shown that full-fat dairy intake measured using the DQES v2 FFQ was positively associated with serum lipid species known to be of ruminant origin (21) , suggesting that this FFQ can be used to estimate dairy intake.…”
Section: Discussionsupporting
confidence: 89%
“…At present, the DQES v2 FFQ has been validated in a cohort of Fe-deficient women (2) and two healthy populations (3,4) , and it is found to have relatively good agreement with a 3-d weighed food record (WFR). It classifies more than two-thirds of subjects within 1 quintile difference for all nutrients compared with a 3-d WFR (3) .…”
mentioning
confidence: 99%
“…That is why in this FFQ some open questions have been added to know if schoolchildren have consumed a fruit or vegetable not listed on it. In general, the correlations observed in the literature ranged from 0.5 to 0.8; this studio has similar correlations except the one for consumption of only fruit [22][23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 54%